Analysis of factors affecting the purchase of private label products by different age consumers. Issue 13 (21st November 2022) - Musso, Fabio; Colamatteo, Annarita; Bravi, Laura; Pagnanelli, Maria Anna; Murmura, Federica; Sansone, Marcello
Abstract : Purpose: The aim of this study is to determine how the different age of consumers impacts on some factors that drive consumers to the purchasing of private label products, considering differences and similarities of behaviors. Design/methodology/approach: The research was conducted through the administration of a questionnaire to evaluate consumers' perceptions about private label food products. To collect data, the convenience sampling method has been used. The valid answers collected and analyzed are 358. Findings: The results of this study highlight that the response of different age groups to the Private Label Brands (PLBs) must be considered in the light of the positioning adopted by the individual retailers. Value for money and satisfaction on previous consumption are relevant for purchasing decisions regardless of the retailer's strategy and the age of consumers. A third factor, price, is important for the whole sample. Focusing on the specific age clusters, the younger respondents seem to be attentive to factors such as healthy and in-store promotion, while the more experienced consumer are attentive to the origin and traceability of products. Originality/value: An analysis of the main literature on Private Labels showed that the results of research about the role of consumer age in PLB choices are contrasting. This study aims at integrating the literature, measuring how the factors influencing the purchase of PLB products vary for different age groups of consumers.